B.O.C Enterprise: B.O.C Multipurpose Cleaner (cleaning product) / Muhammad Shamil Ab. Razak [et al.] - Ab. Razak, Muhammad Shamil; Mohamad Shahir, Muhammad Zaki Ikmal; Sepian, Muhammad Azreen Shah; Abdul Rahman, Muhammad Naqiuddin; Abd Rahim, Muhammad Farhan; Mohamed Salikin, Muhammad Shazni (2017)
B.O.C Enterprise is a company which will ease the citizen in cleaning aspect. This company sells a new type if cleaning product namely Multipurpose Cleaner that undergoes innovation from the current once.